The reasons for the reluctance of the students of the College of Teachers from the individual application within Study room (Journal of the College of Basic Education, 2023)
The art of teaching develops through the relationship that links the principles of effective education with the fields of performance.teachers in the classroom, which is in contrast to the old trends that wereEvaluation of teachers by focusing on the characteristics of teachers as supposed indicators of the effectiveness of education.While we see that the modern approach to teacher evaluation should focus on his ability to translateThe volume of cognitive information related to the art of teaching, which is translated into educational steps.According to the belief of some educators, complete training in the various academic subjects isIt is an essential prerequisite for any serious study of pedagogy, and one of the clear and necessary tasksTo apply this approach, it is necessary to define the parameters of these principles for effective teaching.:28) p. (7.The preparation of the primary school teacher varies greatly from one country to another in terms of the duration of thestudy, enrollment qualifications, quantity of teaching training, and educational materials available atThe teacher at the time of training and the type of study. And since the preparation of the teacher is of great importance before the service, heeducators and supervisors in this aspect effectively through their teaching in institutes andTeachers' colleges...the education process has several requirements, including content, students, and methodsTeaching methods and evaluation methods, and in each requirement, there may be obstacles in achieving them, includingWhat is related to the teacher himself, such as hesitation and anxiety when carrying out the teaching task, and the reason may sometimes be inThis is due to the lack of practical training and lessons during preparation and before actual service.to a lack of information. The rapid and continuous changes in various areas of lifeled to a change in the role of the teacher in the educational process, and specialists in the educational field agreedHowever, the teacher is the cornerstone of the educational process, even if he constitutes one of its elements to createComprehensive change in the behavior and preparations of individuals in order to reach the creation of the citizenThe righteous who is able to serve his community according to its values and traditions.